Pengembangan Literasi Membaca Pada Mata Pelajaran Pendidikan Agama Islam Di SMA N 3 Panyabungan - Aulia Rahmah Puteri; Junaidi Junaidi; Salmiwati Salmiwati; Al Baihaqi Anas (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2023)
The problem in this research is the lack of enthusiasm of students in the learning process, students are lazy to open printed books, lazy to go to the library, limited learning references. The purpose of this study was to describe the Pai learning process, the validity and practicality of developing teaching materials in the form of Reading Literacy Development in Islamic Religious Education Subjects Based on Instagram Social Media in Class X SMA N 3 Panyabung. The method used in this research is research and development. With a 4D approach (Define, Design, Developed, Disseminate). Reading Literacy in Islamic Religious Education Subjects Based on Instagram Social Media in Class X SMA N 3 Panyabung was declared valid by both validators with an overall percentage score of 82.5% being very valid from the two validators. Based on the results of the questionnaire analysis of students' responses to the practicality of using reading literacy in the Pai subject, it was found that this media was practically used in learning with an overall acquisition of 85%. The item statement obtained an average questionnaire value of 84.63%. with very practical information. Based on the results of the validity and practicality that has been carried out by researchers on reading literacy in Pai learning based on Instagram social media for class X SMA 3 Panyabungan can be used in the learning process.